Capitals and Citadels of Bronze-Iron Age Syria in their Relationship to Land and Water - van Liere, Willem J.
I. Introduction; II. The Beginnings of Settlement; III. The City State; IV. The Fertile Regions of Syria; V. Retarded Proto-Urban Areas; VI. “Inter-State” Organization; VII. New Prospects for the Identification of Šubat Enlil, Washukhanni and Arpad; VIII. The Classical Era.